Fluorescent functionalized bionic magnetic bead and preparation method thereof

By preparing spiky magnetic beads with a hydrophobic polymer core, magnetic nanoparticles, and fluorescent molecules, the problems of small specific surface area and unsatisfactory adsorption effect of existing magnetic beads have been solved. Fluorescent functionalized biomimetic magnetic beads with uniform particle size and good adsorption effect have been realized, which are suitable for the biomedical field.

CN120944024APending Publication Date: 2025-11-14苏州仿生材料科学与工程中心
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511033009.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

The existing magnetic bead surface structure is difficult to construct, resulting in a small specific surface area, unsatisfactory adsorption effect, and inability to quickly determine the adsorption and elution effect. Furthermore, there is a lack of products on the market that simultaneously possess fluorescent signals and magnetic responses.

Method used

A fluorescent functionalized biomimetic magnetic bead was prepared by using a hydrophobic polymer core, magnetic nanoparticles, hydrophobic fluorescent molecules, and a hydrophilic spiky structure. The spiky structure was formed through an emulsification polymerization reaction, combining superparamagnetism and luminescence.

Benefits of technology

The magnetic beads exhibit uniform particle size, large surface area, and good adsorption effect, enabling rapid assessment of adsorption status and possessing luminescence properties, making them suitable for the biomedical field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944024A_ABST
    Figure CN120944024A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorescent functionalized bionic magnetic bead and a preparation method thereof. The magnetic bead preparation method comprises the following steps: 1) dissolving a hydrophobic monomer, a hydrophobic polymer, an initiator and fluorescent dye molecules in an organic solvent to obtain a solution A; dispersing magnetic nanoparticles in an organic solvent to obtain dispersion liquid B; 2) uniformly mixing the solution A and the dispersion solution B, adding a surfactant aqueous solution, and emulsifying to obtain an oil-in-water emulsion C; 3) dissolving a hydrophilic monomer in the surfactant aqueous solution to obtain a solution D; and mixing the oil-in-water emulsion C with the solution D, introducing nitrogen, heating, carrying out polymerization reaction, washing the product, and carrying out freeze drying to obtain the product. The magnetic beads show superparamagnetism and luminescence, and are uniform in particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of immunomagnetic bead preparation technology, specifically to a fluorescent functionalized biomimetic magnetic bead and its preparation method. Background Technology

[0002] With the development of science and technology, the enrichment and purification of specific target substances, especially the separation and purification of trace substances, are becoming increasingly important in the field of biomedical research. Polymer microspheres coated with magnetic particles, known as magnetic beads, possess unique adsorption and separation functions, making them suitable as tools for the extraction and purification of biomolecules such as DNA. They also serve as media for virus isolation, demonstrating broad application potential in medical testing. In the biomedical field, the applications of magnetic beads encompass both diagnostics and treatment. In diagnostics, magnetic beads can detect specific biomarkers by surface-coupled specific antibodies; while in treatment, guided by external magnetic fields in instruments, magnetic beads can carry drugs and achieve precise release within the body.

[0003] While magnetic beads have shown great potential in medical testing, certain problems still exist. Current technologies typically produce core-shell silicon-shell magnetic beads with smooth surfaces. The difficulty in constructing these surface structures results in a small specific surface area, limiting the number of binding sites for biomarkers such as DNA and leading to unsatisfactory adsorption. Furthermore, the reliance on magnetically responsive markers necessitates multiple steps of adsorption and elution for separation and purification, making it difficult to quickly determine whether adsorption and elution of the marker have been successful.

[0004] In the current microsphere market, some suppliers mainly offer magnetic beads with smooth magnetic core polymer microspheres, and very few products incorporate fluorescent signals into the magnetic beads; while other suppliers offer fluorescent microsphere products that simply incorporate fluorescent dye molecules without containing magnetic nanoparticles that enable the microspheres to have a magnetic response. Therefore, this invention is derived from this. Summary of the Invention

[0005] In order to solve at least one of the above-mentioned technical problems, the present invention aims to provide a fluorescent functionalized biomimetic magnetic bead and its preparation method. The fluorescent magnetic bead has a uniform particle size, and the process is relatively simple and controllable. The surface modification is simple and can be mass-produced, and it can be applied to multiple fields.

[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0007] One objective of this invention is to provide a fluorescent functionalized biomimetic magnetic bead comprising a hydrophobic polymer core, magnetic nanoparticles dispersed on the surface, hydrophobic fluorescent molecules distributed within and on the surface of the polymer core, and hydrophilic spiky structures distributed on the surface, exhibiting a large specific surface area; the magnetic bead exhibits superparamagnetism and luminescence. The prepared magnetic bead exhibits superparamagnetism and can be applied in the biomedical field; the prepared magnetic bead also exhibits luminescence. Preferably, the luminescence includes red fluorescence, blue fluorescence, green fluorescence, etc.

[0008] Furthermore, the diameter of the hydrophobic polymer core is 100 nm to 100 μm; and / or

[0009] The hydrophobic polymer core is made of one or more of the following materials: polystyrene, poly(α-methylstyrene), poly(o-chlorostyrene), polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride.

[0010] Furthermore, the material of the hydrophilic spiky structure is selected from one or more of sodium polyacrylate, sodium polymethacrylate, sodium polyitacrylate, sodium polymaleate, sodium polyvinyl sulfonate, sodium polystyrene sulfonate, and sodium polystyrene carboxylate.

[0011] Furthermore, the magnetic nanoparticles have a particle size of 1 nm to 100 nm; and / or

[0012] The magnetic nanoparticles are selected from one or more of the following: iron(II,III) oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron-platinum nanoparticles, cobalt triplatide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles; and / or

[0013] The fluorescent dye molecule is selected from one or more of the following: Rhodamine Green, Rhodamine 6G, Tetramethylrhodamine, Rhodamine B, X-Rhodamine, FITC, FAM, AMCA, Courmarin 343, Cy2, Cy3, Cy3.5, Cy5, Cy5.5, Cy7, Cy7.5, BODIPY FL, BODIPY 493 / 503, and BODIPY 530 / 550.

[0014] Another object of the present invention is to provide a method for preparing fluorescent functionalized biomimetic magnetic beads, comprising the following steps:

[0015] Step 1) Dissolve the hydrophobic monomer, hydrophobic polymer, initiator and fluorescent dye molecules in an organic solvent to obtain solution A; disperse the magnetic nanoparticles in an organic solvent to obtain dispersion B.

[0016] Step 2): Mix solution A and dispersion B obtained in step 1) evenly according to the formula amount, and add the formula amount of surfactant aqueous solution for emulsification to obtain oil-in-water emulsion C;

[0017] Step 3) Dissolve the hydrophilic monomer in an aqueous surfactant solution to obtain solution D; mix the oil-in-water emulsion C obtained in step 2) with solution D according to the formula amount, purge with nitrogen and heat to evaporate the organic solvent. After the polymerization reaction is completed, wash the product obtained from the polymerization reaction and freeze dry to obtain the fluorescent functionalized biomimetic magnetic beads.

[0018] Furthermore, in step 1),

[0019] The hydrophobic polymer has a weight-average molecular weight of 5000 g / mol to 60000 g / mol, preferably including but not limited to 5000 g / mol to 60000 g / mol, 10000 g / mol to 50000 g / mol, and 20000 g / mol to 40000 g / mol; and / or

[0020] In solution A, the concentration of the hydrophobic polymer is 0.05 mg / mL to 500 mg / mL; including but not limited to 0.05 mg / mL to 400 mg / mL, 0.1 mg / mL to 500 mg / mL, 5.0 mg / mL to 200 mg / mL; and / or

[0021] In solution A, the mass of the hydrophobic polymer is 50 mg to 400 mg, preferably including but not limited to 50 mg to 100 mg, 100 mg to 200 mg, and 50 mg to 400 mg; the mass ratio of the hydrophobic monomer to the hydrophobic polymer is 50 to 100:1, preferably including but not limited to 50 to 80:1 and 80 to 100:1; the mass ratio of the hydrophobic monomer to the fluorescent dye molecule is 100 to 1000:1, preferably including but not limited to 100 to 400:1, 200 to 500:1, and 600 to 1000:1; the molar ratio of the hydrophobic monomer to the initiator is 5 to 100:1, for example, such as 5 to 20:1, 5 to 50:1, and 50 to 100:1; and / or

[0022] In dispersion B, the mass ratio of the magnetic nanoparticles to the organic solvent is 5~50:1, preferably including but not limited to 5~10:1, 10~20:1, and 20~50:1; and / or

[0023] The mass ratio of the hydrophobic monomer in solution A to the magnetic nanoparticles in dispersion B is 10~300:1, preferably including but not limited to 10~300:1, 50~200:1, and 80~150:1.

[0024] Furthermore, in step 1),

[0025] The hydrophobic monomer includes one or more of styrene, α-methylstyrene, o-chlorostyrene, divinylbenzene, methyl methacrylate, ethyl methacrylate, ethylene, and vinyl chloride; and / or

[0026] The hydrophobic polymer includes one or more of polystyrene, poly(α-methylstyrene), poly(o-chlorostyrene), polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride; and / or

[0027] The initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobiscyclohexylformitrile, benzoyl peroxide, and tert-butyl peroxide; and / or

[0028] The fluorescent dye molecules include one or more of the following: Rhodamine Green, Rhodamine 6G, Tetramethylrhodamine and Rhodamine B, X-Rhodamine, 9-vinylanthracene, FITC, FAM, AMCA, Courmarin 343, Cy2, Cy3, Cy3.5, Cy5, Cy5.5, Cy7, Cy7.5, BODIPY FL, BODIPY 493 / 503, and BODIPY 530 / 550; and / or

[0029] In solution A, the organic solvent includes one or more of benzene, toluene, xylene, chlorobenzene, dichloromethane, and chloroform; and / or

[0030] The magnetic nanoparticles include one or more of the following: iron(II,III) oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron-platinum nanoparticles, cobalt triplatide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles; and / or

[0031] In dispersion B, the organic solvent includes one or more of dichloromethane, methanol, and ethanol.

[0032] Furthermore, in step 2),

[0033] The mixing ratio of solution A to dispersion B is 0.005~0.05:1, preferably including but not limited to 0.005~0.01:1, 0.01~0.05:1; and / or

[0034] The mixing temperature of solution A and dispersion B is 15 ℃~35 ℃, and the mixing time is 10 min~10 h; and / or

[0035] The surfactant concentration in water is 0.0005 g / mL to 0.05 g / mL, preferably including but not limited to 0.001 g / mL to 0.05 g / mL, 0.0005 g / mL to 0.05 g / mL, 0.001 g / mL to 0.05 g / mL, and 0.01 g / mL to 0.05 g / mL; and / or

[0036] The surfactant includes one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, polyvinyl alcohol, and polyethylene glycol.

[0037] Furthermore, in step 3),

[0038] The mass ratio of the oil-in-water emulsion C to the solution D is 0.1~0.8:1, preferably including but not limited to 0.1~0.5:1, 0.4~0.8:1, and 0.5:1; and / or

[0039] The molar ratio of the hydrophilic monomer to the hydrophobic monomer in step 1) is 1:(0.1~200), preferably including but not limited to 1:(0.1~200), 1:(0.5~200), 1:(1.0~150), 1:(5.0~100), 1:(10.0~80); and / or

[0040] The molar ratio of the hydrophilic monomer to the initiator in step 1) is 1:(0.01~0.1), preferably including but not limited to 1:(0.01~0.1), 1:(0.02~0.09), 1:(0.03~0.08), 1:(0.04~0.07), 1:0.05; and / or

[0041] The surfactant concentration in water is 0.0005 g / mL to 0.05 g / mL, preferably including but not limited to 0.001 g / mL to 0.05 g / mL, 0.0005 g / mL to 0.05 g / mL, 0.001 g / mL to 0.05 g / mL, and 0.01 g / mL to 0.05 g / mL; and / or

[0042] In solution D, the mass ratio of the hydrophilic monomer to the surfactant is 20-100:1, preferably including but not limited to 30-50:1, 20-45:1, and 50-100:1; and / or

[0043] Nitrogen gas was introduced for 5 to 60 minutes, the polymerization temperature was 50 to 80 ℃, and the polymerization time was 2 to 24 hours.

[0044] Furthermore, in step 3),

[0045] The hydrophilic monomer includes one or more of sodium acrylate, sodium methacrylate, sodium itaconic acid, sodium maleate, sodium vinyl sulfonate, sodium styrene sulfonate, sodium styrene carboxylate, and sodium styrene borate; and / or

[0046] The surfactant comprises one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, polyvinyl alcohol, and polyethylene glycol; and / or

[0047] The detergents used for washing the products obtained from the polymerization reaction include one or more of methanol, ethanol, acetone, n-hexane, and deionized water.

[0048] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0049] The fluorescent functionalized biomimetic magnetic beads of this invention have uniform particle size, and the process is relatively simple and controllable. Surface modification is easy and large-scale mass production is possible, making them applicable to multiple fields. Compared to existing smooth-surfaced magnetic core polymer microspheres, the fluorescent functionalized biomimetic magnetic beads of this invention have a spiky structure on their surface, resulting in a larger specific surface area, more available binding sites, and better adsorption. The magnetic beads exhibit superparamagnetism and luminescence, and possess magnetic responsiveness, making them suitable for applications in the biomedical field. Attached Figure Description

[0050] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0051] Figure 1 This is a scanning electron microscope image of the green fluorescent functionalized biomimetic magnetic beads prepared in Example 1 of the present invention;

[0052] Figure 2 This is a fluorescence microscope image of the green fluorescent functionalized biomimetic magnetic beads prepared in Example 1 of the present invention;

[0053] Figure 3 This is a fluorescence microscope image of the red fluorescent functionalized biomimetic magnetic beads prepared in Example 3 of the present invention;

[0054] Figure 4This is a fluorescence microscope image of the blue fluorescent functionalized biomimetic magnetic beads prepared in Example 4 of the present invention;

[0055] Figure 5 The magnetization curve of the green fluorescent functionalized biomimetic magnetic beads prepared in Example 1 of this invention is shown.

[0056] Figure 6 This is a transmission electron microscope image of the green fluorescent functionalized biomimetic magnetic beads prepared in Example 1 of the present invention;

[0057] Figure 7 This is a scanning electron microscope image of the red fluorescent functionalized biomimetic magnetic beads with non-uniform particle size prepared in Comparative Example 1 of the present invention.

[0058] Figure 8 This is a fluorescence microscope image of the green fluorescent functionalized biomimetic magnetic bead with excessively low fluorescence intensity prepared in Comparative Example 2 of this invention. Detailed Implementation

[0059] In view of the shortcomings of the existing technology, the inventors of this case, through long-term research and extensive practice, have proposed a fluorescent functionalized biomimetic magnetic bead and its preparation method.

[0060] The following description, in conjunction with preferred embodiments and accompanying drawings, further explains and illustrates the technical solution, its implementation process, and its principles. It should be particularly noted that the following embodiments are merely illustrative of the invention and should not be construed as limiting the scope of protection of the invention.

[0061] Example 1

[0062] This embodiment provides a method for preparing green fluorescent functionalized biomimetic magnetic beads, including the following steps:

[0063] 1) Mix 100 mg polystyrene, 1 mL styrene, 250 μL methyl methacrylate, 1 mg FITC, 1 mL dichloromethane, and 20 mg azobisisobutyronitrile, and sonicate for 30 min to obtain solution A;

[0064] 2) Add 20 mg of iron oxide nanoparticles to 2 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0065] 3) Add 900 mg of sodium acrylate to 15 mL of a 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain solution D;

[0066] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 50 mL of 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain oil-in-water emulsion C;

[0067] 5) Mix oil-in-water emulsion C with solution D, heat to 50 °C to evaporate the solvent for 1 h, purge with nitrogen for 10 min, and then stir and heat at 75 °C for 16 h to carry out polymerization;

[0068] 6) After the reaction is complete, the product is washed four times with methanol and deionized water and then freeze-dried.

[0069] See Figure 1 The synthesized product, characterized by SEM, exhibited a spiky surface structure, good magnetic bead dispersion, uniform size, and an average particle size of 2.7 μm; see [link to SEM]. Figure 5 The saturation magnetization of the synthesized product, characterized by VSM, was approximately 2.33 (emu / g); see [link to VSM]. Figure 2 The synthesized product, as characterized by fluorescence microscopy, emitted bright green fluorescence; see also Figure 6 The magnetic nanoparticles added during synthesis were characterized by transmission electron microscopy and found to be distributed on the outer ring of the product.

[0070] Example 2

[0071] This embodiment provides a method for preparing green fluorescent functionalized biomimetic magnetic beads, including the following steps:

[0072] 1) Mix 150 mg polystyrene, 1 mL α-methylstyrene, 250 μL methyl methacrylate, 1 mg FITC, 1 mL dichloromethane, and 20 mg azobisisobutyronitrile, and sonicate for 30 min to obtain solution A;

[0073] 2) Add 20 mg of iron oxide nanoparticles to 2 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0074] 3) Add 900 mg of sodium acrylate to 15 mL of a 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain solution D;

[0075] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 50 mL of 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain oil-in-water emulsion C;

[0076] 5) Mix oil-in-water emulsion C with solution D, heat to 50 °C to evaporate the solvent for 1 h, purge with nitrogen for 10 min, and then stir and heat at 75 °C for 16 h to carry out polymerization;

[0077] 6) After the reaction is complete, the product is washed four times with methanol and deionized water and then freeze-dried.

[0078] The synthesized product, as characterized by SEM, has a spiky structure on its surface, good magnetic bead dispersion, uniform size, and an average particle size of 2.7 μm; the synthesized product, as characterized by fluorescence microscopy, emits bright green fluorescence.

[0079] Example 3

[0080] This embodiment provides a method for preparing red fluorescent functionalized biomimetic magnetic beads, including the following steps:

[0081] 1) Mix 100 mg polystyrene, 1 mL styrene, 250 μL methyl methacrylate, 1 mg Cy3.5, 1 mL dichloromethane, and 20 mg azobisisobutyronitrile, and sonicate for 30 min to obtain solution A;

[0082] 2) Add 20 mg of iron oxide nanoparticles to 2 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0083] 3) Add 900 mg of sodium acrylate to 15 mL of a 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain solution D;

[0084] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 50 mL of 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain oil-in-water emulsion C;

[0085] 5) Mix oil-in-water emulsion C with solution D, heat to 50 °C to evaporate the solvent for 1 h, purge with nitrogen for 10 min, and then stir and heat at 75 °C for 16 h to carry out polymerization;

[0086] 6) After the reaction is complete, the product is washed four times with methanol and deionized water and then freeze-dried.

[0087] The synthesized product, characterized by SEM, exhibited a spiky surface structure, good magnetic bead dispersion, uniform size, and an average particle size of 2.9 μm; see [link to SEM]. Figure 3 The synthesized product, as characterized by fluorescence microscopy, emitted a bright red fluorescence.

[0088] Example 4

[0089] This embodiment provides a method for preparing blue fluorescent functionalized biomimetic magnetic beads, including the following steps:

[0090] 1) Mix 6 mL of α-methylstyrene, 1 mL of dichloromethane, 1 mg of AMCA, 15 mg of azobisisobutyronitrile, and 150 mg of polyethyl methacrylate and ultrasonically disperse for 30 min to obtain solution A;

[0091] 2) Add 30 mg of iron oxide nanoparticles to 3 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0092] 3) Add 150 mg of sodium styrenecarboxylate to 10 mL of a 0.25 wt% aqueous solution of sodium dodecyl sulfonate to obtain solution D;

[0093] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 45 mL of 0.25 wt% sodium dodecyl sulfonate aqueous solution to obtain oil-in-water emulsion C;

[0094] 5) Mix oil-in-water emulsion C with solution D, heat to 45 °C to evaporate the solvent for 30 min, purge with nitrogen for 5 min, and then stir and heat at 70 °C for 20 h to carry out polymerization;

[0095] 6) After the reaction is complete, the product is washed four times with ethanol and deionized water and then freeze-dried.

[0096] SEM characterization revealed that the synthesized product exhibited a spiky surface structure, good magnetic bead dispersion, uniform size, and an average particle size of 6.0 μm; see [link to relevant documentation]. Figure 4 The synthesized product, as characterized by fluorescence microscopy, emitted a bright blue fluorescence.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing red magnetic beads. The ratio of hydrophobic monomer to hydrophobic polymer during the preparation process is outside the range required by the method for preparing fluorescent functionalized biomimetic magnetic beads of this invention. Specifically, the method includes the following steps:

[0099] 1) Mix 50 mg polystyrene, 12 mL styrene, 250 μL methyl methacrylate, 1 mg Cy3.5, 1 mL dichloromethane, and 20 mg azobisisobutyronitrile, and sonicate for 30 min to obtain solution A;

[0100] 2) Add 20 mg of iron oxide nanoparticles to 2 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0101] 3) Add 900 mg of sodium acrylate to 15 mL of a 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain solution D;

[0102] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 50 mL of 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain oil-in-water emulsion C;

[0103] 5) Mix oil-in-water emulsion C with solution D, heat to 50 °C to evaporate the solvent for 1 h, purge with nitrogen for 10 min, and then stir and heat at 75 °C for 16 h to carry out polymerization;

[0104] 6) After the reaction is complete, the product is washed four times with methanol and deionized water and then freeze-dried.

[0105] See Figure 7 The image shows a scanning electron microscope (SEM) image of the magnetic beads prepared in this comparative example. As can be seen from the image, the red magnetic beads prepared in this comparative example have irregular morphology and uneven particle size.

[0106] Comparative Example 2

[0107] This comparative example provides a method for preparing green magnetic beads. The ratio of hydrophobic monomers to fluorescent dye molecules in the preparation process is outside the range required by the method for preparing fluorescent functionalized biomimetic magnetic beads of this invention. Specifically, it includes the following steps:

[0108] 1) Mix 50 mg polystyrene, 10 mL styrene, 250 μL methyl methacrylate, 1 mg Cy2, 1 mL dichloromethane, and 20 mg azobisisobutyronitrile, and sonicate for 30 min to obtain solution A;

[0109] 2) Add 20 mg of iron oxide nanoparticles to 2 mL of dichloromethane and disperse by ultrasonication for 30 min to obtain dispersion B;

[0110] 3) Add 900 mg of sodium acrylate to 15 mL of a 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain solution D;

[0111] 4) Mix solution A with dispersion B, sonicate for 30 min, and then emulsify with 50 mL of 0.25 wt% sodium dodecyl sulfate aqueous solution to obtain oil-in-water emulsion C;

[0112] 5) Mix oil-in-water emulsion C with solution D, heat to 50 °C to evaporate the solvent for 1 h, purge with nitrogen for 10 min, and then stir and heat at 75 °C for 16 h to carry out polymerization;

[0113] 6) After the reaction is complete, the product is washed four times with methanol and deionized water and then freeze-dried.

[0114] See Figure 8 The image shows a fluorescence microscope image of the hydroxyl magnetic beads prepared by the method of this comparative example. As can be seen from the image, the green magnetic beads prepared in this comparative example have weak fluorescence brightness.

[0115] All aspects, embodiments, features, and examples of this invention are to be regarded as illustrative in all respects and are not intended to limit the invention, the scope of which is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0116] Throughout this invention, wherever a composition is described as having, containing, or including specific components, or wherever a process is described as having, containing, or including specific process steps, it is contemplated that the compositions taught in this invention are also substantially composed of or comprised of the described components, and that the processes taught in this invention are also substantially composed of or comprised of the described process steps.

[0117] Unless otherwise specifically stated, the use of the terms “include, include, including” or “have, has, or having” should generally be understood as open-ended and non-restrictive.

[0118] It should be understood that the order of the steps or the order in which specific actions are performed is not particularly important, as long as the teachings of this invention remain operable. Furthermore, two or more steps or actions can be performed simultaneously.

[0119] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims. Moreover, unless specifically stated otherwise, any use of the terms first, second, etc., does not indicate any order or importance, but is used to distinguish one element from another.

Claims

1. A fluorescent functionalized biomimetic magnetic bead, characterized in that, It includes a hydrophobic polymer core, magnetic nanoparticles dispersed on the surface, hydrophobic fluorescent molecules distributed inside and on the surface of the polymer core, and hydrophilic spiky structures distributed on the surface; the magnetic beads exhibit superparamagnetism and luminescence.

2. The magnetic bead according to claim 1, characterized in that, The diameter of the hydrophobic polymer core is 100 nm to 100 μm; and / or The hydrophobic polymer core is made of one or more of the following materials: polystyrene, poly(α-methylstyrene), poly(o-chlorostyrene), polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride.

3. The magnetic bead according to claim 1, characterized in that, The hydrophilic spiky structure is made of one or more of the following materials: sodium polyacrylate, sodium polymethacrylate, sodium polyitacrylate, sodium polymaleate, sodium polyvinyl sulfonate, sodium polystyrene sulfonate, and sodium polystyrene carboxylate.

4. The magnetic bead according to claim 1, characterized in that, The magnetic nanoparticles have a particle size of 1 nm to 100 nm; and / or The magnetic nanoparticles are selected from one or more of the following: iron(II,III) oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron-platinum nanoparticles, cobalt triplatide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles; and / or The fluorescent dye molecule is selected from one or more of Rhodamine Green, Rhodamine 6G, Tetramethylrhodamine, Rhodamine B, X-Rhodamine, FITC, FAM, AMCA, Courmarin 343, Cy2, Cy3, Cy3.5, Cy5, Cy5.5, Cy7, Cy7.5, BODIPY FL, BODIPY493 / 503, and BODIPY 530 / 550.

5. A method for preparing fluorescent functionalized biomimetic magnetic beads, characterized in that, Includes the following steps: Step 1) Dissolve the hydrophobic monomer, hydrophobic polymer, initiator and fluorescent dye molecules in an organic solvent to obtain solution A; disperse the magnetic nanoparticles in an organic solvent to obtain dispersion B. Step 2): Mix solution A and dispersion B obtained in step 1) evenly according to the formula amount, and add the formula amount of surfactant aqueous solution for emulsification to obtain oil-in-water emulsion C; Step 3) Dissolve the hydrophilic monomer in an aqueous surfactant solution to obtain solution D; mix the oil-in-water emulsion C obtained in step 2) with solution D according to the formula amount, purge with nitrogen and heat to evaporate the organic solvent. After the polymerization reaction is completed, wash the product obtained from the polymerization reaction and freeze dry to obtain the fluorescent polymer magnetic beads.

6. The preparation method according to claim 5, characterized in that, In step 1), The hydrophobic polymer has a weight-average molecular weight of 5000 g / mol to 60000 g / mol; and / or In solution A, the concentration of the hydrophobic polymer is 0.05 mg / mL to 500 mg / mL; and / or In solution A, the mass of the hydrophobic polymer is 50 mg to 400 mg, the mass ratio of the hydrophobic monomer to the hydrophobic polymer is 50 to 100:1, the mass ratio of the hydrophobic monomer to the fluorescent dye molecule is 100 to 1000:1, and the molar ratio of the hydrophobic monomer to the initiator is 5 to 100:1; and / or In dispersion B, the mass ratio of the magnetic nanoparticles to the organic solvent is 5~50:1; and / or The mass ratio of the hydrophobic monomer in solution A to the magnetic nanoparticles in dispersion B is 10~300:

1.

7. The preparation method according to claim 6, characterized in that, In step 1), The hydrophobic monomer includes one or more of styrene, α-methylstyrene, o-chlorostyrene, divinylbenzene, methyl methacrylate, ethyl methacrylate, ethylene, and vinyl chloride; and / or The hydrophobic polymer includes one or more of polystyrene, poly(α-methylstyrene), poly(o-chlorostyrene), polydivinylbenzene, polymethyl methacrylate, polyethyl methacrylate, polyethylene, and polyvinyl chloride; and / or The initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobiscyclohexylformitrile, benzoyl peroxide, and tert-butyl peroxide; and / or The fluorescent dye molecules include one or more of the following: Rhodamine Green, Rhodamine 6G, Tetramethylrhodamine and Rhodamine B, X-Rhodamine, 9-vinylanthracene, FITC, FAM, AMCA, Courmarin 343, Cy2, Cy3, Cy3.5, Cy5, Cy5.5, Cy7, Cy7.5, BODIPYFL, BODIPY 493 / 503, and BODIPY 530 / 550; and / or In solution A, the organic solvent includes one or more of benzene, toluene, xylene, chlorobenzene, dichloromethane, and chloroform; and / or The magnetic nanoparticles include one or more of the following: iron(II,III) oxide nanoparticles, γ-iron oxide nanoparticles, manganese oleate nanoparticles, cobalt nanoparticles, nickel nanoparticles, iron-platinum nanoparticles, cobalt triplatide nanoparticles, samarium cobalt 1:5 type magnet nanoparticles, magnesium ferrite nanoparticles, manganese ferrite nanoparticles, and cobalt ferrite nanoparticles; and / or In dispersion B, the organic solvent includes one or more of dichloromethane, methanol, and ethanol.

8. The preparation method according to claim 5, characterized in that, In step 2), The mixing ratio of solution A to dispersion B is 0.005~0.05:1; and / or The mixing temperature of solution A and dispersion B is 15 ℃~35 ℃, and the mixing time is 10 min~10 h; and / or The surfactant concentration in water is 0.0005 g / mL to 0.05 g / mL; and / or The surfactant includes one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, polyvinyl alcohol, and polyethylene glycol.

9. The preparation method according to claim 5, characterized in that, In step 3), The mass ratio of the oil-in-water emulsion C to the solution D is 0.1~0.8:1; and / or The molar ratio of the hydrophilic monomer to the hydrophobic monomer in step 1) is 1:(0.1~200); and / or The molar ratio of the hydrophilic monomer to the initiator in step 1) is 1:(0.01~0.1); and / or The surfactant concentration in water is 0.0005 g / mL to 0.05 g / mL; and / or In solution D, the mass ratio of the hydrophilic monomer to the surfactant is 20~100:1; and / or Nitrogen gas was introduced for 5 to 60 minutes, the polymerization temperature was 50 to 80 ℃, and the polymerization time was 2 to 24 hours.

10. The preparation method according to claim 9, characterized in that, In step 3), The hydrophilic monomer includes one or more of sodium acrylate, sodium methacrylate, sodium itaconic acid, sodium maleate, sodium vinyl sulfonate, sodium styrene sulfonate, sodium styrene carboxylate, and sodium styrene borate; and / or The surfactant comprises one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, polyvinyl alcohol, and polyethylene glycol; and / or The detergents used for washing the products obtained from the polymerization reaction include one or more of methanol, ethanol, acetone, n-hexane, and deionized water.